Comparative study between the effect of television advertising, social media of instagram, and brand image in the decision of purchasing new product - Curana, Randhika; Khomariah, Nurul Isti; Bagaskara, Rafif Edratama Aji; Mani, La; Aras, Muhammad (Linguistics and Culture Review, 2022)
Television advertising is one of the most effective methods used by companies to introduce and give information about a product to their target consumers. However, as technology advances in the early 2000s, the number of internet users in the world and Indonesia has increased annually. There are currently 160 million Indonesian people who are actively using social media, whose spending 3 hours 26 minutes using social media and 3 hours 4 minutes watching television. The current study was carried out in investigating the effect of television advertising, social media, and brand image on consumers' decisions in purchasing new products. In this case, the researcher collected data from 250 respondents who used aromatherapy wind oil throughout Indonesia. The results of this study are expected to be used to improve the manufacture of advertising media plans that will be used by companies in the current digitalization era. The results of this study indicated that the role of television advertising greatly influences purchasing decisions compared to Instagram social media for a new product.